2021
DOI: 10.1016/j.system.2021.102494
|View full text |Cite
|
Sign up to set email alerts
|

Multiword sequences in English language learners’ speech: The relationship between trigrams and lexical variety across development

Abstract: Languages have formulaic multiword sequences (MWSs) that occur repeatedly in speech and writing (e.g., Nattinger & DeCarrico, 1992; Siyanova-Chanturia & Pellicer-Sanchez, 2018). For learners, then, the production of MWSs is an important element in developing spoken language which is complex, accurate, and fluent. However, though the use of MWSs are important for achieving spoken proficiency, it is unclear whether the production of MWSs supports or hinders another aspect of proficiency, lexical variety. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Since formulaic sequences fall into the scope of formulaic language, to a large degree, the positive relationship between the use of formulaic language and oral fluency could mirror the positive relationship between the use of formulaic sequences and oral fluency. These results could correspond well to the findings that formulaic sequences play a crucial role in language use (Boers and Webb, 2018;Wang, 2018;Liu and Chen, 2020;Shin, 2020;Vercellotti et al, 2021;Fritz et al, 2022;Kim and Kessler, 2022).…”
Section: Empirical Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Since formulaic sequences fall into the scope of formulaic language, to a large degree, the positive relationship between the use of formulaic language and oral fluency could mirror the positive relationship between the use of formulaic sequences and oral fluency. These results could correspond well to the findings that formulaic sequences play a crucial role in language use (Boers and Webb, 2018;Wang, 2018;Liu and Chen, 2020;Shin, 2020;Vercellotti et al, 2021;Fritz et al, 2022;Kim and Kessler, 2022).…”
Section: Empirical Studiessupporting
confidence: 90%
“…All these reflect the roles of formulaic sequences in language learning through the mechanism of proceduralization. Many studies have indeed showcased the importance of formulaic sequences in language use (Boers and Webb, 2018;Wang, 2018;Liu and Chen, 2020;Shin, 2020;Vercellotti et al, 2021;Fritz et al, 2022;Kim and Kessler, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The last variable within this line is time. Studies of this category ( Siyanova-Chanturia, 2015 ; Hyland and Jiang, 2018 ; Hong, 2019 ; Candarli, 2021 ; Vercellotti et al, 2021 ) investigate whether bundle use change over time. An exemplary study is Hyland and Jiang (2018) research which explored the changes of bundles in four disciplines from 1965 to 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, the relationship between bundles and complexity is less obvious because existing studies seem to report contradictory results. Some studies ( Mellow, 2006 ; Taguchi, 2008 ; Ma, 2020 ) found a positive effect of bundles on complexity, whereas others ( Vercellotti et al, 2021 ) fail to observe such an effect.…”
Section: Introductionmentioning
confidence: 98%